Structural investigations of phosphorus-nitrogen compounds. 6. Relationships between molecular parameters in per-X-substituted bridged spermine derivatives and basicity constants ??R of substituents - Coles, SJ; Davies, DB; Hursthouse, MB; Kiliç, A; Mayer, TA; Shaw, RA; Çiftçi, Y (Int Union Crystallography, 2004)
A systematic study is reported of the products of the nucleophilic substitution reactions of the spermine-bridged cyclotriphosphazene, [N3P3X4(NHCH2CH2CH2N)CH2CH2](2) [where X = Cl (2a)], to give a number of new structures [(2b)-(2g)] in which X = OPh, [spiro-O(CH2)(3)O](0.5), Ph, NHPh, NC4H8 and NHBut, respectively. A comparison has been made between the sum of the substituent basicity constants, Sigmaalpha(R), obtained in nitrobenzene solution, and ten molecular parameters of the N3P3 ring ( the internal bond angles alpha, beta, gamma, delta and theta, and the P-N bond lengths a, b, c, d and e) as well as the difference between the bond lengths a and b, Delta(P-N). It is found that the systematic change in molecular parameters of compounds (2a)-(2g) is in line with changes in alpha(R) values, indicating the similarity in relative electron-releasing capacity of substituents X in the solid state and in solution. It is also found that the effect on molecular parameters of (2a)-(2g) with two X substituents in PX2 groups is greater than that for one X substituent in P(OR)X groups in an analogous series of compounds observed previously.
Keywords: Ray Crystallography; Crystal-Structure; Phenyl; Hexachlorocyclotriphosphazatriene; Cyclotriphosphazatrienes; Phenyltriphosphonitriles; Amino